Physico Chemical,Nutritional and Toxicological Evaluation of Thermally Oxidised Edible Oils - Rekha Francis C (Department of Home Science, College of Agriculture, 1994)
“Physico chemical, nutritional and toxicological evaluation of thermally oxidized edible oils” were determined by assessing their changes in physical and chemical properties, nutritional changes ie changes in fatty acid composition and toxic as well as mutagenic effect in relation to reheated oils taking fresh oils as check.